Barriers to 'equal pay for work of equal value' for women in Japan: Assessing the potential for change. (September 2020) - Beniyama, Ayaka
This article examines barriers to the principle of equal remuneration for work of equal value in Japan, reviewing impediments to the implementation of the International Labour Organisation's Equal Remuneration Convention, and assessing whether the 2018 Work Style Reform Act–which seeks to reduce pay disparities between regular and non-regular workers through a Japanese version of 'equal pay for equal work'–provides an alternative avenue through which stronger notions of work value and equality might become integrated into Japanese wage-setting norms and practices. This has implications for the gender pay gap, which could be addressed more effectively within a regulatory framework recognising equal pay for equal (value) work as a legal norm, as well as narrowed indirectly through improving remuneration for non-regular workers (the majority of whom are women). The analysis highlights the limits of the new legislative measures, arguing that in spite of some potential for improving pay for non-regular workers, they lack important features conducive to the pursuit of gender pay equality, in particular non-biased concepts of value, effective job evaluation models and a more inclusive gender/human rights perspective.